(untitled) (Journal of Computational Mathematics, 2018)
This paper covers the review and some aspects of using Multigrid method for fluid dynamics problems. The main development stages of multigrid technics are presented. Some approaches for solving Navier-Stokes equations and convection-diffusion problems are considered.